Toxin‐Induced Liver Injury Following Bear Bile Consumption in a Middle‐Aged Female in Bhutan: A Case Report - Sonam Wangzin Rabjay; Thai Wangmo; Thinley Dorji (Clinical Case Reports)
ABSTRACT Consumption of bear bile can cause severe hepatotoxicity. Clinicians should consider toxin‐mediated liver injury in patients with unexplained jaundice. Early recognition, discontinuation of the offending agent, and potential use of N‐acetylcysteine and ursodeoxycholic acid may aid recovery. Public awareness and regulation of traditional remedies may help in the prevention of harm to patients.